2012
DOI: 10.1007/s12104-012-9404-z
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific 1H, 13C and 15N NMR assignments of Cyclophilin A like protein from Piriformospora indica involved in salt stress tolerance

Abstract: Cyclophilins are omnipresent proteins found in eukaryotes and prokaryotes, with presence in cytoplasm as well as in nucleus. Primary role of Cyclophilins is of peptidyl-prolyl cis-trans isomerase, a molecular chaperon action. Here, we report sequence-specific (1)H, (13)C and (15)N resonance assignments for a Cyclophilin A like protein from Piriformospora indica. This protein is up-regulated during salt stress conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…50 Recently we have also reported the sequence-specific 1 H, 13 C and 15 N NMR assignments and preliminary X-ray crystallographic analysis of Cyclophilin A like protein from Piriformospora indica. 51,52 In case of the expression analysis under different developmental stages, the Arabidopsis cyclophilin genes exhibited higher response to the senescence conditions. Role of a copper chaperon has also been reported in senescence previously.…”
Section: Discussionmentioning
confidence: 99%
“…50 Recently we have also reported the sequence-specific 1 H, 13 C and 15 N NMR assignments and preliminary X-ray crystallographic analysis of Cyclophilin A like protein from Piriformospora indica. 51,52 In case of the expression analysis under different developmental stages, the Arabidopsis cyclophilin genes exhibited higher response to the senescence conditions. Role of a copper chaperon has also been reported in senescence previously.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated order parameter by analyzing NMR relaxation parameters R 1 , R 2 , and 15 N-{ 1 H} nOe. Complete sequence-specific NMR resonance assignments of the protein have been reported previously22. We had observed that chemical shifts of amide protons of L34 (10.67 ppm), D88 (11.36 ppm) and H95 (10.74 ppm) and amide nitrogen of E89 (132.8 ppm) are unusually downfield shifted.…”
Section: Resultsmentioning
confidence: 52%
“…In the 2D [ 15 N, 1 H] HSQC spectra except for minor changes in chemical shifts of surface exposed residues T55, S80 and K85 no significant backbone amide chemical shift perturbations (CSPs) were observed confirming that structural integrity of the protein is maintained even at 600 mM NaCl22.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…We solved the crystal structure of PiCypA and demonstrated that it contains a canonical cyclophilin fold (Figure 17.8) [76] (PBD ID: 4EYV). Using solution-state NMR spectroscopy we showed that PiCypA retains its structural integrity even at high concentrations of Na þ [77]. PiCypA contains no additional RNA-recognizing motif, but it still binds to RNA.…”
Section: Stabilization Of Proteins and Rnasmentioning
confidence: 99%